2020
DOI: 10.1055/s-0040-1710531
|View full text |Cite
|
Sign up to set email alerts
|

ALK 1 Negative Inflammatory Myofibroblastic Tumor of the Ileum: A Rare Cause of Ileocecal Intussusception

Abstract: AbstractAn inflammatory myofibroblastic tumor is a rare tumor of mesenchymal background commonly found in the pulmonary system. It is rarely found as a primary tumor in the gastrointestinal tract. We report an unusual presentation of this rare lesion causing intussusception and intestinal obstruction in a 39-year-old male.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition, several diseases, including Crohn's disease, congenital neutropenia, gastrointestinal stromal tumor, and pregnancy have been related to the development of IMT (16). Previous studies have reported the correlation between ALK-1 gene expression and local recurrence, distant metastasis, and overall prognosis of IMT patients (17)(18)(19)(20). Moreover, in certain studies (8,21,22), the bladder IMT was associated with the Epstein-Barr virus, bacteria such as Campylobacter Equi, the human herpes virus HHV8, Campylobacter jejuni, Escherichia coli, trauma, radioand steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several diseases, including Crohn's disease, congenital neutropenia, gastrointestinal stromal tumor, and pregnancy have been related to the development of IMT (16). Previous studies have reported the correlation between ALK-1 gene expression and local recurrence, distant metastasis, and overall prognosis of IMT patients (17)(18)(19)(20). Moreover, in certain studies (8,21,22), the bladder IMT was associated with the Epstein-Barr virus, bacteria such as Campylobacter Equi, the human herpes virus HHV8, Campylobacter jejuni, Escherichia coli, trauma, radioand steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity and resistance in tumor cells can reduce therapy efficacy. When ALK inhibition is not an option for ALK-negative tumors, the nonsteroidal anti-inflammatory drugs (NSAIDs) have been helpful [ 16 ]. It is also postulated that NSAIDs may shrink tumors and perhaps cure cancer [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…When ALK inhibition is not an option for ALK-negative tumors, the nonsteroidal anti-inflammatory drugs (NSAIDs) have been helpful [ 16 ]. It is also postulated that NSAIDs may shrink tumors and perhaps cure cancer [ 16 ]. Corticosteroids are also effective in young children with bilateral renal-infiltrating IMT.…”
Section: Discussionmentioning
confidence: 99%